2021
DOI: 10.1371/journal.pone.0253902
|View full text |Cite
|
Sign up to set email alerts
|

Unconditioned and learned morphine tolerance influence hippocampal-dependent short-term memory and the subjacent expression of GABA-A receptor alpha subunits

Abstract: Background ɣ-aminobutyric acid (GABA) facilitator valproic acid may be able to curb memory disruption induced by morphine exposure. Objective The effects of the GABA facilitator valproic acid on the behavioral tolerance induced by morphine were investigated. Then hippocampal-dependent tasks named spatial-working and short-term memory procedures using the Y-maze apparatus were examined in morphine tolerant rats. Finally, the changes in the expression of hippocampal GABA-A receptors underlying morphine toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…We found that RME increased GABA A α1 and α5 mRNA levels in the DH. The findings of our previous study also indicate an increase in the mRNA level of hippocampal GABAα1 during non-associative morphine tolerance development in rats (Ghamkharinejad et al, 2021). Others have reported significant mRNA up-regulation of the epsilon subunit of the GABA A receptor in locus coeruleus neurons during morphine withdrawal (Heikkilä et al, 2001).…”
Section: Rme Increases the Expression Of Gaba A Receptor α1 And α5 Su...supporting
confidence: 69%
“…We found that RME increased GABA A α1 and α5 mRNA levels in the DH. The findings of our previous study also indicate an increase in the mRNA level of hippocampal GABAα1 during non-associative morphine tolerance development in rats (Ghamkharinejad et al, 2021). Others have reported significant mRNA up-regulation of the epsilon subunit of the GABA A receptor in locus coeruleus neurons during morphine withdrawal (Heikkilä et al, 2001).…”
Section: Rme Increases the Expression Of Gaba A Receptor α1 And α5 Su...supporting
confidence: 69%
“…Learning can contribute to opiate tolerance and the conditioning analysis of morphine tolerance indicates the occurrence of context-specific tolerance. [4][5][6] The hippocampus is perhaps the most iconic brain region associated with learning and memory (Kutlu et al, 2016) and it has been hypothesized that the dH and vH may have distinct roles in the different forms of learning and memory. By measuring neurogenesis and dendritic plasticity in the dH and vH, our study shows that morphine tolerance is associated with hippocampus subregion specific changes in neurogenesis and dendritic remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological mechanisms underlying the initiation and development of opiate tolerance remain still elusive, which prevents the discovery of effective and sustained pain relief methods. Learning can contribute to opiate tolerance and the conditioning analysis of morphine tolerance indicates the occurrence of context‐specific tolerance 4–6 . The hippocampus is perhaps the most iconic brain region associated with learning and memory (Kutlu et al, 2016) and it has been hypothesized that the dH and vH may have distinct roles in the different forms of learning and memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations